2009
DOI: 10.1007/s11269-009-9423-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Evapotranspiration Equations Under Humid Conditions

Abstract: Five reference evapotranspiration (ET 0 ) equations are evaluated using data from seven humid locations. The equations evaluated include Hargreaves, Thornthwaite, Turc, Priestley-Taylor, and Jensen-Haise. The objective of this study is to evaluate ET 0 estimated by these equations against the corresponding values estimated using the standardized FAO-56 Penman-Monteith (PM) equation. For each location, ET 0 estimates by the all equations were statistically compared with FAO-56 PM ET 0 estimates. The Turc equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
79
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 19 publications
(28 reference statements)
12
79
2
3
Order By: Relevance
“…Conceição & Mandelli (2005), studying ETo values estimated with the empirical equations and compared to the FAO-PM method, concluded that the methods employing only air temperature, such as Hargreaves-Samani and Thornthwaite, showed poorer results than the others for the city of Bento Gonçalves, RS, Brazil. This result was also observed by Trajkovic & Kolakovic (2009), when they compared five ETo equations against FAO-PM using data from seven humid locations in Croatia and Serbia; the equations ranked in decreasing order were: Turc, Priestley-Taylor, Jensen-Haise, Thornthwaite, and Hargreaves. Reis et al (2007) also found the worst performance of the Hargreaves-Samani method compared to the FAO-PM on a daily scale; therefore, there is a restriction of its use for the weather conditions in the three localities of Espírito Santo State, Brazil during the dry period.…”
Section: Resultssupporting
confidence: 61%
“…Conceição & Mandelli (2005), studying ETo values estimated with the empirical equations and compared to the FAO-PM method, concluded that the methods employing only air temperature, such as Hargreaves-Samani and Thornthwaite, showed poorer results than the others for the city of Bento Gonçalves, RS, Brazil. This result was also observed by Trajkovic & Kolakovic (2009), when they compared five ETo equations against FAO-PM using data from seven humid locations in Croatia and Serbia; the equations ranked in decreasing order were: Turc, Priestley-Taylor, Jensen-Haise, Thornthwaite, and Hargreaves. Reis et al (2007) also found the worst performance of the Hargreaves-Samani method compared to the FAO-PM on a daily scale; therefore, there is a restriction of its use for the weather conditions in the three localities of Espírito Santo State, Brazil during the dry period.…”
Section: Resultssupporting
confidence: 61%
“…Hargreaves equation was also the best model to estimate ETo in eastern arid and semiarid regions of Iran [31]. [32] indicated that the Turc equation was the best in the Western Balkans in Europe. [22] reported that Hansen and Turc equations were the most useful for ETo estimation in Greece.…”
Section: Introductionmentioning
confidence: 90%
“…It was also found to significantly overestimate ET in this study area, and the relative errors were respectively around 59 and 48%. Such overestimation also occurred in the humid regions of Serbia [30] and Florida of the USA [31]. …”
mentioning
confidence: 89%